Rice OVERLY TOLERANT TO SALT 1 (OTS1) SUMO protease is a positive regulator of seed germination and root development. (3rd May 2016) - Srivastava, Anjil Kumar; Zhang, Cunjin; Sadanandom, Ari
ABSTRACT: Salinity is one of the major environmental stresses affecting rice production worldwide. Improving rice salt tolerance is a critical step for sustainable food production. Posttranslational modifications of proteins greatly expand proteome diversity, increase functionality and allow quick responses to environmental stresses, all at low cost to the cell. SUMO mediated modification of substrate proteins is a highly dynamic process governed by the balance of activities of SUMO E3 ligases and deconjugating SUMO proteases. In recent years, SUMO (Small Ubiquitin like Modifier) conjugation of proteins has emerged as an influential regulator of stress signaling in the model plant Arabidopsis. However SUMOylation remain largely under studied in crop plants. We recently identified the SUMO protease gene family in rice and demonstrated a role for OsOTS1 SUMO proteases in salt stress. Interestingly, rice plants silencing OsOTS1 also show significantly reduced germination rate. Knockdown of OsOTS1 gene expression affects root growth by primarily reducing cell size rather than cell division.